Prevalence of dental Fluorosis and its epidemiological determinants in a Hilly state of India- A Cross-Sectional Study - Sharma, Nidhi; Saxena, Vartika; Singh, Pallavi; Katre, Rohit; Naithani, Manisha; Dhar, Minakshi (Indian Journal of Community Health, 2025)
Background: From a human health perspective, fluorine acts as a double-edged sword as its deficiency leads to dental caries, while excess fluorine intake is associated with the development of fluorosis (dental and skeletal). Aims and Objectives: This study was conducted with the aim of assessing the prevalence of dental fluorosis associated with different water fluoride concentrations (naturally occurring sources). Additionally, sociodemographic, lifestyle and anthropometric measurements were analyzed to determine their association with the prevalence of dental fluorosis. Methodology: A cross-sectional study was conducted for 12 months in children aged 6-19 years in the Rudraprayag district of Uttarakhand. The fluorosis assessment was done as per Dean’s index. The sample size was 1400. Data was collected using a predesigned, pretested, semi-structured questionnaire by personal interview method. A p-value of < 0.05 was considered statistically significant. Results: Overall prevalence of dental fluorosis was 19.1% (267/1400). Surprisingly, 39% of these cases of fluorosis were drinking water within normal fluoride range (0.5 mg/l- 1.0 mg/l). Only 4 villages out of thirty reported having more than 1 mg/l fluoride content in the drinking water. The children of higher socioeconomic status, class 2 and above, had 1.78 times more chances of being affected by fluorosis than children of lower socioeconomic status (p = 0.015, 1.78 (1.12 - 2.83)). Dental fluorosis was twice more common among stunted children (p = 0.011, 2.08 (1.16 – 3.73)). Conclusion: For the first time, this study reported the occurrence of dental fluorosis in Uttarakhand. Fluorosis was reported even if water fluoride concentration was below 1mg/liter may be due to high altitude of the region.